PERBANDINGAN NILAI RATA-RATA SKOR SKALA STROKE GADJAH MADA (SSGM) PULANG PADA PASIEN STROKE BERDASAR FAKTOR RISIKO TUNGGAL DAN MULTIPEL - , MARIA NOVA NURFITRI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Stroke is one of the leading causes of mortality and disability in the world. Based on the high incindence and the burden of strokeâs complication, it is important to study various risk factors associated with this disease. Multiple risk factor is assumed to be correlated to poor outcome. Objective: The objective of this study is to compare the means of discharge-SSGM score in stroke patients based on single and multiple risk factors. Method: This study is an analitical observational study which is conducted retrospectively with the approach of cross sectional method. Result: From 60 subjects, 31 (51,7%) subjects are men and 29 (48,3%) subjects are women. According to the type of stroke, 14 (23,3%) subjects suffer from hemorrhagic stroke and 46 (76,7%) subjects suffer from ischemic stroke. According to the type of risk factor, 43 (71,7%) subjects have the history of hypertension, 10 (16,7%) subjects have the history smoking, 14 (23,3%) subjects have the history of stroke/TIA, 7 (11,7%) subjects have the history of heart disease, 17 (28,3%) have the history of dyslipidemia, and 11 (18,3%) subjects have the history diabetes melitus. The mean of discharge-SSGM score of subjects with single risk factor is 30,37 and 26,80 for subject with multiple risk factor. The difference between these two group is significant (p=0,033